DITA - Kay, Russell (Computerworld, 2007)
The Darwin Information Typing Architecture (DITA) uses XML as the basis for designing, writing, managing and publishing many kinds of information, both in print and on the Web. A strength of DITA is its ability to be extended to cover new areas of knowledge through specific, targeted document type definitions. DITA is organized around the notion of the topic, defined as a unit of information that describes a single task, concept or reference item, or a chunk of information organized around a single subject. To collect and organize references to DITA topics and indicate relationships among topics, DITA uses a simple mapping mechanism. By definition, knowledge expands, and DITA allows for new types of knowledge through a process called specialization.